'My life and my inspiration': Meštrović, folklore and symbolic sculpture. (2016) - Hopkins, Justine
Abstract : In 1915 the Victoria and Albert Museum held an exhibition of work by Ivan Meštrović, 'the Southern Slav sculptor'. Afterwards the Serbian government donated to the museum one of the works exhibited, Torso of Banović Strahinja, Meštrović's image of the legendary folk hero. Since then the work has been displayed with reference to the influence of Rodin on Meštrović in his superbly carved, fragmentary figure of an enigmatic hero. This article proposes that the Torso be considered not only as a superb piece of craftsmanship nor as merely an example of modernist aesthetics, but in context as part of Meštrović's projected Temple of Kosovo; that it is founded on the artist's profound knowledge of Serbian history and folklore, and informed by his passion for the cause of national unity and by his stated belief in the duty of the artist to contribute to humankind's spiritual development through symbolic works. So considered, fragmentation is essential to the meaning of the piece, and subject, technique and form interact to create a symbolic image conceived to convey the essential human truths at the heart of an ancient legend.